Climate-responsive DNA methylation is involved in the biosynthesis of lignin in birch - Chen, Bowei; Guo, Yile; Zhang, Xu; Wang, Lishan; Cao, Lesheng; Zhang, Tianxu; Zhang, Zihui; Zhou, Wei; Xie, Linan; Wang, Jiang; Sun, Shanwen; Yang, Chuanping; et al. (Frontiers in Plant Science, 2022)
Lignin is one of the most important secondary metabolites and essential to the formation of cell walls. Changes in lignin biosynthesis have been reported to be associated with environmental variations and can influence plant fitness and their adaptation to abiotic stresses. However, the molecular mechanisms underlying this association remain unclear. In this study, we evaluated the relations between the lignin biosynthesis and environmental factors and explored the role of epigenetic modification (DNA methylation) in contributing to these relations if any in natural birch. Significantly negative correlations were observed between the lignin content and temperature ranges. Analyzing the transcriptomes of birches in two habitats with different temperature ranges showed that the expressions of genes and transcription factors (TFs) involving lignin biosynthesis were significantly reduced at higher temperature ranges. Whole-genome bisulfite sequencing revealed that promoter DNA methylation of two NAC-domain TFs, BpNST1/2 and BpSND1, may be involved in the inhibition of these gene expressions, and thereby reduced the content of lignin. Based on these results we proposed a DNA methylation-mediated lignin biosynthesis model which responds to environmental factors. Overall, this study suggests the possibility of environmental signals to induce epigenetic variations that result in changes in lignin content, which can aid to develop resilient plants to combat ongoing climate changes or to manipulate secondary metabolite biosynthesis for agricultural, medicinal, or industrial values.